Kānprayuk chai rabop sārasonthēt phūmisāt phư̄a kānwikhro̜ læ wāngphǣn čhatkān phư̄nthī sīang phai din thalom/nam pā lailāk : kō̜ranī sưksā ʻAmphœ̄ Dān Sāi, Čhangwat Lœ̄i. (Samnak Wičhai læ Khwāmrūammư̄ Rawāng Prathēt, Sūn Thēknōlōyī Sārasonthēt, Krom Pō̜ngkan læ Banthao Sāthāranaphai, 2010)
Application of remote sensing and Geographic Informaion System to monitor, analyze, and plan for landslides and sudden floods in Loei Province, Northeastern Thailand.